Therapist beliefs about exposure therapy implementation. (2020) - Meyer, Johanna M.; Kelly, Peter J.; Deacon, Brett J.
Abstract: Exposure therapy is consistently indicated as the first-line treatment for anxiety-related disorders. Unfortunately, therapists often deliver exposure therapy in an overly cautious, less effective manner, characterized by using their own 'therapist safety behaviours'. Cognitive behavioural models postulate that beliefs about therapist safety behaviours are related to their use; however, little is known about the beliefs therapists hold regarding therapist safety behaviour use. The present study aimed to identify the beliefs exposure therapists have regarding the necessity of therapist safety behaviours and to examine the relationship between this construct and therapist safety behaviour use. Australian psychologists ( n = 98) completed an online survey that included existing measures of therapist safety behaviour use, therapist negative beliefs about exposure therapy, likelihood to exclude anxious clients from exposure therapy, and use of intensifying exposure techniques. Participants also completed the Exposure Implementation Beliefs Scale (EIBS), a measure created for the present study which assesses beliefs regarding the necessity of therapist safety behaviours. Beliefs about the necessity of therapist safety behaviours – particularly in protecting the client – significantly predicted therapist safety behaviour use. Findings suggest that exposure therapy training media should aim to decrease therapist safety behaviour use by addressing beliefs about the necessity of therapist safety behaviours, especially in protecting the client. Key learning aims: (1) To understand what therapist safety behaviours are in the context of exposure therapy. (2) To identify common beliefs about therapist safety behaviours. (3) To understand how beliefs about therapist safety behaviours relate to therapist safety behaviour use. (4) To consider how exposure therapy delivery may be improved by modifying beliefs about therapist safety behaviours. (5) To explore how beliefs about therapist safety behaviours may be modified to reduce therapist safety behaviour use.